REKSA DANA SEBAGAI SALAH SATU ALTERNATIF INVESTASI - Meilinda . (Bina Ekonomi, 2010)
An investor always search for the best investment to protect and grow his/her wealth. There are many investment instruments that provide high-return with high-risk and vice versa. Choosing the right instrument for an investor may depend on the risk profiles, amount of fund, time horizon, knowledge and the goal to achieve.  Despite of the risks, mutual/investment fund is one of the profitable investment  instruments.Keywords : investment, return, risk profiles, mutual investment  fund